Structure of an adenine-cytosine base pair in DNA and its implications for mismatch repair. - Hunter, W; Brown, T; Anand, N; Kennard, O (1986)
Mutational pathways rely on introducing changes in the DNA double helix. This may be achieved by the incorporation of a noncomplementary base on replication or during genetic recombination, leading to substitution mutation. In vivo studies have shown that most combinations of base-pair mismatches can be accommodated in the DNA double helix, albeit with varying efficiencies. Fidelity of replication requires the recognition and excision of mismatched bases by proofreading enzymes and post-replicative mismatch repair systems. Rates of excision vary with the type of mismatch and there is some evidence that these are influenced by the nature of the neighbouring sequences. However, there is little experimental information about the molecular structure of mismatches and their effect on the DNA double helix. We have recently determined the crystal structures of several DNA fragments with guanine X thymine and adenine X guanine mismatches in a full turn of a B-DNA helix and now report the nature of the base pairing between adenine and cytosine in an isomorphous fragment. The base pair found in the present study is novel and we believe has not previously been demonstrated. Our results suggest that the enzymatic recognition of mismatches is likely to occur at the level of the base pairs and that the efficiency of repair can be correlated with structural features.